1987
DOI: 10.13031/2013.26665
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Midwestern Soybeans

Abstract: Soybeans, from the 1983 and 1984 crops, were analyzed for official grade-factors, protein/oil composition, and breakage susceptibility. Samples were collected from 13 locations across four states. U.S. Grades did not differ greatly between years or sample origins, but nutrients and breakage susceptibility did. The average protein and oil percentages, basis 13.0% moisture, were 33.9, 19.7 and 34.2, 19.1 for 1983 and 1984 respectively. Several equations were developed to interrelate quality factors. For a one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The concentrations of these two components are genetically predetermined but can vary depending on the environment [18]. The protein and oil content of soybean seeds are negatively correlated [19,20]. A higher temperature during reproductive growth tends to result in higher oil content [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of these two components are genetically predetermined but can vary depending on the environment [18]. The protein and oil content of soybean seeds are negatively correlated [19,20]. A higher temperature during reproductive growth tends to result in higher oil content [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the effects of year and location on oil content were both significant, but that there was little effect of either on protein content. Hurburgh et al (1987) studied soybean samples from grain elevators in four states of the United States. The oil concentration of soybean was higher in the hotter, drier year and the soybean samples with highest contents of oil were from the area with the most severe drought.…”
mentioning
confidence: 99%
“…The typical trade between producers and elevators and elevators and processors are stand-alone decisions not involving composition. Elevators and processors pay based on U.S. Grades of test weight, moisture, and foreign material, not on protein and oil content (Hurburgh et al, 1987;Laux et al, 2015). This procedure takes place despite the importance of protein and oil content for end users (Brumm and Hurburgh, 2006;Medic et al, 2014).…”
mentioning
confidence: 99%